Association of hepatitis C viral infection with incidence and progression of chronic kidney disease in a large cohort of US veterans. Issue 5 (20th March 2015) - Molnar, Miklos Z.; Alhourani, Hazem M.; Wall, Barry M.; Lu, Jun L.; Streja, Elani; Kalantar‐Zadeh, Kamyar; Kovesdy, Csaba P.
Abstract : An estimated 4 million Americans have been exposed to the hepatitis C virus (HCV). The risks of incident and progressive chronic kidney disease and of mortality in patients with normal kidney function infected with HCV are unclear. In a nationally representative cohort of 100, 518 HCV + and 920, 531 HCV – US veterans with normal baseline estimated glomerular filtration rate (eGFR), we examined the association of HCV infection with (1) all‐cause mortality, (2) incidence of decreased kidney function (defined as eGFR <60 mL/min/1.73 m 2 and 25% decrease in eGFR), (3) end‐stage renal disease, and (4) rate of kidney function decline. Associations were examined in naive and adjusted Cox models (for time‐to‐event analyses) and logistic regression models (for slopes), with sequential adjustments for important confounders. Propensity‐matched cohort analysis was used in sensitivity analyses. The patients' age was 54.5 ± 13.1 (mean ± standard deviation) years, 22% were black, 92% were male, and the baseline eGFR was 88 ± 16 mL/min/1.73 m 2 . In multivariable adjusted models HCV infection was associated with a 2.2‐fold higher mortality (fully adjusted hazard ratio = 2.17, 95% confidence interval [CI] 2.13‐2.21), a 15% higher incidence of decreased kidney function (adjusted hazard ratio = 1.15, 95% CI 1.12‐1.17), a 22% higher risk of steeper slopes of eGFR (adjusted odds ratio = 1.22, 95% CI 1.19‐1.26), and a 98% higher hazard of end‐stage renal disease (adjusted hazard ratio = 1.98, 95% CI 1.81‐2.16). Quantitatively similar results were found in propensity‐matched cohort analyses. Conclusions : Infection with HCV is associated with higher mortality risk, incidence of decreased kidney function, and progressive loss of kidney function; randomized controlled trials are warranted to determine whether treatment of HCV infection can prevent the development and progression of chronic kidney disease and improve patient outcomes. (Hepatology 2015;61:1495–1502)